GAYA BELAJAR ANAK USIA DINI DALAM PROSES PEMBELAJARAN DI RA NUR QOMARIAH JAMPANGTENGAH SUKABUMI - Irma Muti; Nurlela; Puji Riani; Robi'ah Ahadiyah; Siti Sodariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the characteristics of early childhood learning styles and explore how teachers accommodate these differences in the learning process at RA Nur Qomariah Jampangtengah, Sukabumi. Although numerous studies have examined the influence of learning styles on learning outcomes, limited research has qualitatively explored the contextual implementation of learning style accommodation in Islamic early childhood education settings. This study employed a qualitative descriptive approach involving Group B students and classroom teachers as primary informants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldana interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that children demonstrate diverse learning styles, namely visual, auditory, and kinesthetic, with kinesthetic tendencies being the most dominant. Children showed higher engagement and comprehension when learning activities involved direct experience and play-based interaction. The study also indicates that while teachers have attempted to implement varied instructional strategies to accommodate these differences, challenges remain in terms of limited learning media and class size. This research contributes empirically to the understanding of differentiated learning practices in RA contexts by highlighting the importance of flexible and integrative instructional design. The findings suggest that integrating visual, auditory, and kinesthetic elements in a balanced manner can foster a more inclusive and developmentally appropriate learning environment in early childhood education.